2022
DOI: 10.3389/fcimb.2022.933824
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera (L.) Dunal (Ashwagandha) for the possible therapeutics and clinical management of SARS-CoV-2 infection: Plant-based drug discovery and targeted therapy

Abstract: Coronavirus disease 2019 (COVID-19) pandemic has killed huge populations throughout the world and acts as a high-risk factor for elderly and young immune-suppressed patients. There is a critical need to build up secure, reliable, and efficient drugs against to the infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Bioactive compounds of Ashwagandha [Withania somnifera (L.) Dunal] may implicate as herbal medicine for the management and treatment of patients infected by SARS-CoV-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 138 publications
(109 reference statements)
0
8
0
Order By: Relevance
“…The literature survey suggests that Withania somnifera has important molecular and pharmacological characteristics to act as a therapeutic adjuvant for prophylaxis and treatment of COVID‐19 (Singh et al, 2022). Many of the bioactive compounds of Withania somnifera such as Withanone and Withaferin A have potential to inhibit the interaction between RBD of SARS‐CoV‐2 Spike‐protein and ACE2 receptor (Maurya & Sharma, 2020; Saggam et al, 2021).…”
Section: Pharmacology Of Different Herbs and Spices Used In Kwath Pre...mentioning
confidence: 99%
“…The literature survey suggests that Withania somnifera has important molecular and pharmacological characteristics to act as a therapeutic adjuvant for prophylaxis and treatment of COVID‐19 (Singh et al, 2022). Many of the bioactive compounds of Withania somnifera such as Withanone and Withaferin A have potential to inhibit the interaction between RBD of SARS‐CoV‐2 Spike‐protein and ACE2 receptor (Maurya & Sharma, 2020; Saggam et al, 2021).…”
Section: Pharmacology Of Different Herbs and Spices Used In Kwath Pre...mentioning
confidence: 99%
“…WS, a shrub traditionally used in India and other Asian countries, is known to possess immunomodulatory properties. Previous in-vitro and in-vivo studies have shown that WS could play a role in the regulation of inflammation by suppressing pro-inflammatory cytokines ( 21 24 ). More recently, in-silico docking studies showed the potent inhibitory potential of Withanone, an active ingredient of WS, against SARS-CoV-2 virulence proteins such as spike protein ( 22 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive metabolites of Withania somnifera possess adaptogenic, anticancer, anti-convulsant, immunomodulatory, antioxidative and neurological effects. The plant has also been found to be efficient in the treatment of osteo-arthritis, geriatric, behavioural and anxiety ( Singh et al., 2022 ). The root extract of Ashwagandha containing withanolide A is reported to have health promoting effects such as anti-stress, anti-arthiritic, anti-inflammatory, analgesic, anti-pyretic, anti-oxidant and immunomodulatory properties ( Singh et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plant has also been found to be efficient in the treatment of osteo-arthritis, geriatric, behavioural and anxiety ( Singh et al., 2022 ). The root extract of Ashwagandha containing withanolide A is reported to have health promoting effects such as anti-stress, anti-arthiritic, anti-inflammatory, analgesic, anti-pyretic, anti-oxidant and immunomodulatory properties ( Singh et al., 2022 ). Withanolide B, D, F and withanosides (glycosylated steroids) secreted by WS having neuroprotective, anticancer, hepatoprotective, anti-aging, diuretic, antipogenic, hemopoietic, immunomodulatory functions and antioxidant activities ( Singh et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation